2014
DOI: 10.1051/mmnp/20149605
|View full text |Cite
|
Sign up to set email alerts
|

A 2D Mathematical Model of Blood Flow and its Interactions in an Atherosclerotic Artery

Abstract: A stenosis is the narrowing of the artery, this narrowing is usually the result of the formation of an atheromatous plaque infiltrating gradually the artery wall, forming a bump in the ductus arteriosus. This arterial lesion falls within the general context of atherosclerotic arterial disease that can affect the carotid arteries, but also the arteries of the heart (coronary), arteries of the legs (PAD), the renal arteries... It can cause a stroke (hemiplegia, transient paralysis of a limb, speech disorder, sai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Since we are interested in studying the flow in the coronary arteries, we decided to use a non-Newtonian flow model like in [3] and [2]. In fact, the coronary arteries have a small caliber (0.5 cm) compared to the aorta for example, where the use of non-Newtonian flow model is not really crucial.…”
Section: Fractional Flow Reservementioning
confidence: 99%
See 3 more Smart Citations
“…Since we are interested in studying the flow in the coronary arteries, we decided to use a non-Newtonian flow model like in [3] and [2]. In fact, the coronary arteries have a small caliber (0.5 cm) compared to the aorta for example, where the use of non-Newtonian flow model is not really crucial.…”
Section: Fractional Flow Reservementioning
confidence: 99%
“…In our case, the blood cannot be assimilated to a Newtonian fluid, since the coronary vessels caliber is very small (0.5 cm). We choose a non-Newtonian flow model, as in [3]. The mathematical model was studied in [3] and authors proved the existence of a solution to this type of problems.…”
Section: Generalized Non-newtonian Flow Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…One can find an attempt in [2], where, after a 2D analytical study to prove the existence of a weak solution for incompressible non-Newtonian fluids with non standard BCs, the authors tested the model numerically by coupling it with a nonlinear hyperelastic model for the arterial wall and the atheromatous plaque, with different values of Young modulus corresponding to each structure. They showed that considering the classical models of interaction between the blood flow (modeled as a Newtonian fluid), the vessel wall and the atherosclerotic plaque, the risk of rupture is less predictive because it underestimates the stress over the plaque comparing with the case where blood is modeled as a non-Newtonian fluid.…”
mentioning
confidence: 99%